(3GdQbGHI Ydi JOGhd GdChQGb GdeGdjI hOhQgG aj QaY caGAI Shb GdeGd (B/s - (3Rjf GdYGHOjf MTeJ GdMSjfs; (3gGfj UdGM SQj GdOjfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2025)
(3JgOa gPg GdOQGSI Edi HjGf OhQ GdQbGHI Ydi JOGhd GdChQGb GdeGdjI aj JYRjR caGAI Shb GdeGd(B. (3hJJfGhd GdOQGSI GdQbGHI GdMchejI GdJj JeGQSgG GdLgGJ GdeNJUI eKd GdgjFI GdYGeI ddQbGHI GdeGdjI hGdHhQUI GdeUQjI, ef NdGd GdQbGHI GdSGHbI hGddMXjI hGddGMbI Ydi YedjGJ GdJOGhd, MjK Je JSdjW GdVhA Ydi OhQ Jdc GdLgGJ aj GdQbGHI Ydi GdTQcGJ GdYGedI aj eLGd JOGhd GdChQGb GdeGdjI, hGdJj JTed TQcGJ GdSeSQI aj GdChQGb GdeGdjI, hTQcGJ GdEjOGY hGdbjO GdeQcRj(B. (3hPdc Edi LGfH GdQbGHI GdPGJjI GdJj JdJRe HgG gPg GdTQcGJ HZQV GdJMbb ef JWHjb GdbhGfjf hGddhGFM GdJfajPjI hGdbQGQGJ GdUGOQI JfajPkG dg, dVeGf JMbjb GdYOGdI hGdeSGhGI aj GdShb hMeGjI Mbhb heUGdM GdeJYGedjf, hGdMaGX Ydi GSJbQGQ GdeYGedGJ ajgG(B.s
This study aims to demonstrate the role of securities trading supervision in enhancing the efficiency of the capital market. The study addresses the governmental supervision exercised by the competent authorities, such as the Financial Regulatory Authority and the Egyptian Stock Exchange, through prior, immediate and subsequent supervision of trading operations. The role of these authorities in supervising companies operating in the field of securities trading was highlighted, which includes securities brokerage firms, depository and central registry companies. This is in addition to the self-supervision that these companies are committed to in order to verify the implementation of laws, executive regulations and decisions issued in implementation thereof, to ensure the achievement of justice and equality in the market, protect the rights and interests of dealers, and maintain the stability of transactions therein.
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb , bSe GdbGfhf GdJLGQj, (B2025s
(3HHdjhLQGajG(B: (3UaMGJ (B294-309s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdJLGQjs; (3caGAI Shb GdeGds; (3GdEWGQ GdbGfhfjs; (3GdQbGHI Ydi Shb GdeGds; (3GdeeGQSGJ ZjQ GdeTQhYIs; (3GdeVGQHI GdeTQhYIs; (3GdHhQUI s; (3ELQGAGJ GdJaJjTs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs